Graphene/Si-nanowire heterostructure molecular sensors - Kim, Jungkil (Nature Publishing Group, 2014)
Wafer-scale graphene/Si-nanowire (Si-NW) array heterostructures for molecular sensing have been fabricated by vertically contacting single-layer graphene with high-density Si NWs. Graphene is grown in large scale by chemical vapour deposition and Si NWs are vertically aligned by metal-assisted chemical etching of Si wafer. Graphene plays a key role in preventing tips of vertical Si NWs from being bundled, thereby making Si NWs stand on Si wafer separately from each other under graphene, a critical structural feature for the uniform Schottky-type junction between Si NWs and graphene. The molecular sensors respond very sensitively to gas molecules by showing 37 and 1280% resistance changes within 3.5/0.15 and 12/0.15 s response/recovery times under O(2) and H(2) exposures in air, respectively, highest performances ever reported. These results together with the sensor responses in vacuum are discussed based on the surface-transfer doping mechanism.